The Urgency of Strategic Human Resources Planning for the Transformation of the Indonesian National Army Command and Staff College - I Made Suryawan; Eko Sakapurnama (Dinasti Publisher, 2024)
Organizational transformation seems to be a trend amidst the current developments in various organizational strategic environments. Demands for organizational transformation also occur in military organizations. With Indonesia's military capabilities needing to continue to be improved, the transformation of Sesko TNI into a Military Strategy School is one of the areas of focus. In the context of this transformation, the role of human resource management is highly expected. Considering that the Sesko TNI will be transformed into the Military Strategy School, strategic human resource planning for the future has an important position. Therefore, this journal article proposes to analyze the urgency of strategic human resource planning so that it can contribute to the Sesko TNI organization being competitively superior in the future. Apart from that, competency variables that influence the quality of strategic human resource planning are also discussed. By applying literature studies, this article shows the results that it is important for Sesko TNI to implement strategic human resource planning considering the great urgency in the process of implementing strategic human resource planning, Sesko TNI is required to pay serious attention to the competence of planners so that quality of planning can be presented.